The China Australia Geological Storage of CO2 (CAGS) Project: An example of bilateral cooperation and successful capacity building. (November 2018) - Feitz, Andrew; Wang, Hang; Zhong, Ping; Zhang, Xian; Yang, Yang; Zhang, Jiutian; Gurney, Jessica; Huang, Liling; Kalinowski, Aleks; Causebrook, Rick; Barrett, Andrew
Abstract: The China Australia Geological Storage of CO₂ (CAGS) Project is a collaborative project that aims to accelerate the development and deployment of geological storage of carbon dioxide in China and Australia. There are four main programs under CAGS to build CCS capabilities in both countries: research projects, technical workshops, training schools, and scholarly exchanges. All have contributed in advancing CCS/CCUS knowledge and building capability in China and Australia. Now in its third phase and its 10th year, CAGS is regarded as a successful bilateral project, which has produced essential research for advancing CCUS in China, established a strong network for Australian and Chinese researchers and institutions, and contributed to advancing CCUS globally. The paper describes the history of the collaboration and impact of this successful bilateral project.